2010
DOI: 10.2109/jcersj2.118.406
|View full text |Cite
|
Sign up to set email alerts
|

Fracture toughness of dental zirconia before and after autoclaving

Abstract: The purpose of this study was to evaluate the low temperature aging degradation (LTAD) of two types of zirconia through the determination of fracture toughness before and after autoclaving. The fracture toughness of yttria stabilized tetragonal zirconia polycrystals (Y-TZP) and zirconia/alumina nanocomposite stabilized with cerium oxide (Ce-TZP/Al 2 O 3 nanocomposite, so called NANOZR) were determined by Single Edge V-Notch Beam (SEVNB) method before and after autoclaving at 134°C for 5 h. The fracture surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 21 publications
0
19
0
1
Order By: Relevance
“…For example, a flexural strength of 900-1,200 MPa was recorded for Y-TZP in vitro, which is higher than the flexural strength for other dental alloys 7) . Despite the success of zirconia and its variegated applications, it has now become apparent that zirconia ceramics also have a drawback, in that they have a propensity to undergo low-temperature degradation (LTD) in the presence of moisture [8][9][10][11][12][13] . This is a kinetic phenomenon in which the polycrystalline tetragonal material slowly transforms into monoclinic zirconia over a rather narrow but important temperature range, typically between room temperature and approximately 400°C, depending on the stabilizer used, its concentration, and the grain size of the ceramic.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a flexural strength of 900-1,200 MPa was recorded for Y-TZP in vitro, which is higher than the flexural strength for other dental alloys 7) . Despite the success of zirconia and its variegated applications, it has now become apparent that zirconia ceramics also have a drawback, in that they have a propensity to undergo low-temperature degradation (LTD) in the presence of moisture [8][9][10][11][12][13] . This is a kinetic phenomenon in which the polycrystalline tetragonal material slowly transforms into monoclinic zirconia over a rather narrow but important temperature range, typically between room temperature and approximately 400°C, depending on the stabilizer used, its concentration, and the grain size of the ceramic.…”
Section: Introductionmentioning
confidence: 99%
“…This is a kinetic phenomenon in which the polycrystalline tetragonal material slowly transforms into monoclinic zirconia over a rather narrow but important temperature range, typically between room temperature and approximately 400°C, depending on the stabilizer used, its concentration, and the grain size of the ceramic. This phase transformation is followed by microcracking and loss of strength [11][12][13] . In the application of zirconia to dental restorations, there is concern about its degradation when constantly used in a humid atmosphere at body temperature over a long period of time and when it is autoclaved for sterilization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These superior mechanical properties exhibited by zirconia ceramics are attributed to the stress-induced transformation from the tetragonal to monoclinic phase and its release during crack propagation 10) . Ce-TZP/A are more susceptible to stress-induced transformation than Y-TZP 11,12) . Y-TZP have a few problems concerning the low temperature aging degradation (LTAD) caused by phase transformation 10,13) , whereas Ce-TZP/A have complete resistance to LTAD 11,12,14) .…”
Section: Introductionmentioning
confidence: 94%
“…The toughness, strength, and hardness of this nanocomposite are two to three times those of conventional Y-TZP 5) . Ban et al have shown its general superiority as a dental restorative material over myriad commercial dental ceramics [6][7][8][9] . For use in crowns and bridges, the surface of zirconia is generally veneered with feldspathic porcelain to compensate for its insufficient translucency.…”
Section: Introductionmentioning
confidence: 99%